Achieving service portability using self-adaptive data paths. - Zhuoqing, M.M (IEEE Communications magazine)
There is a growing demand for service access through heterogeneous devices attached to diverse networks. For ease of deployment, it is crucial to provide application-level support for transparent roaming and ubiquitous service access. We discuss how to develop such a service infrastructure integrating a variety of telephony arid data services spanning diverse access networks reaching heterogeneous end devices. We describe our techniques for achieving goals of transparent network- and device-independent service access, as well as scalable and fault-tolerant access to composed service entities across the wide area using self-adaptive data paths. We evaluate our implementation through applications that require adaptation to end devices and resource variations. The applications include Universal Inbox, Interactive Voice Room Control, MP3 Jukebox access using a cell phone, and real-time video delivery to wireless clients